Unveiling Moringa oleifera: potent source of antioxidant and antibacterial properties - Deepali Deepali; Vibhuti Gulia; Sahil Singh Dhull; Deepak Beniwal; Jyoti Rani; Gholamreza Abdi (Discover Applied Sciences)
Abstract Medicinal plants, like Moringa oleifera, popularly known as the Miracle Tree, are cherished worldwide for their rich phytochemical profile, and antibacterial, and antioxidant properties that allow them to successfully prevent a variety of diseases. Although M. oleifera leaves are rich in bioactive compounds including flavonoids and phenolics, the efficiency of their extraction varies based on the solvent employed. This study assessed how M. oleifera leaves phytochemical content, antioxidant capacity, and antibacterial properties were affected by water, ethanol, and methanol solvents. The phenolic content (162.49 mg GAE/g) and flavonoid (110.32 mg QE/g) contents were highest in the ethanolic extract, according to spectrophotometric analysis. Seven bioactive chemicals were found by Gas Chromatography and Mass Spectroscopy (GC–MS), and the ethanolic extract’s important functional groups were validated by Fourier-Transform Infrared spectroscopy. Assays for antioxidants showed the ethanolic extract had the lowest IC50 values for 2,2-diphenyl-1-picrylhydrazyl (47.50 µg/mL) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) ABTS (49.32 µg/mL), with strong antibacterial activity against all tested microbes. The study concludes that the yield and bioactivity of M. oleifera extracts are greatly influenced by the kind of solvent used, with ethanol being the most efficient. These results propose possible uses of M. oleifera leaves in the pharmaceutical and nutraceutical industries and advance our knowledge of solvent optimization for optimizing the extraction of bioactive compounds. Furthermore, this study offers fresh perspectives on the bioactive characteristics of M. oleifera from the Sirsa region, emphasizing its unrealized potential for further study and industrial uses.